Research on the Mechanism of Mongolian Medical Warm Acupuncture in Alleviating Insomnia by Increasing the BCL-2/BAX Ratio and Decreasing the Hormones Related to the Central HPA Axis of the Stress Response - Bao, Lidao; Yuan, Hongwei; Si, Lengge; Wang, Yuehong; Chen, Yingsong; Bo, Agula (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
Background Mongolian medical warm acupuncture is efficacious in treatment of insomnia but the mechanism still remains unclear. There is no research on the effect on the changes in expression of mRNA in the receptors of 5HT, DA, 5HT1α, 5HT2α, and DRD2 and the levels of hormones related to the central HPA axis in the stress response.Objective To further explain the mechanism of Mongolian medical warm acupuncture in insomnia treatment and its role in protecting cerebral neurons, elaborate the effect of Mongolian medical warm acupuncture on the changes in expression of 5HT, DA, 5HT1α, and 5HT2α at different sites in the brains of the PCPA-induced insomnia model rats and the levels of hormones related to the central HPA axis in the stress response.Method 72 Wistar rats were randomly divided into blank group, model group, Mongolian medical warm acupuncture group, and diazepam group of 18 each. The rats were intraperitoneally injected with PCPA (400 mg/kg) for 2 consecutive days to induce insomnia. The sleep latency and sleep duration before and after treatment were observed. The content of 5HT in the hypothalamus and hippocampus was measured with the ELISA method. The content of mRNA in the 5HT1A and 5HT2A receptors in the hypothalamus and hippocampus with the qPCR technique. The content of DA in the hypothalamus and corpus striatum was determined with the ELISA method. The content of ELISA in the hypothalamus and the content of ACTH in the serum of the insomnia rats were determined with the ELISA method. The changes in content of the BCL-2 and BAX proteins in the hippocampus were observed with the immunohistochemical method.Result PCPA intraperitoneal injections were able to prolong the sleep latency of the rats and shorten the sleep duration (P<0.05) when compared with the blank group. Mongolian medical warm acupuncture was able to alleviate the tendency of decreasing weight gain arising from insomnia (P<0.05). Mongolian medical warm acupuncture was able to decrease the levels of CRH and ACTH in the hormones related to central HPA axis in the stress response (P=0.017, P=0.015) and alleviate the overexciting state of the HPA axis arising from insomnia. Mongolian medical warm acupuncture group was able to up-regulate the expression of the BCL-2 protein in the hippocampus, down-regulate the expression of the BAX protein, and increase the BCL-2/BAX ratio (P=0.011). Mongolian medical warm acupuncture was able to protect the hippocampal neurons by changing the content of the apoptosis factors (P=0.024).Conclusion Mongolian medical warm acupuncture decreases the levels of CRH and ACTH in the hormone related to the HPA axis, up-regulates the expression of the BCL-2 protein in the hippocampus, and down-regulates the expression of the BAX protein for improving rat insomnia by influencing the expression of 5HT1A and 5HT2A receptors in the hypothalamus and hippocampus.
Keywords: insomnia; Mongolian medical warm acupuncture; 5HT1A; 5HT2; D2; HPA axis